Effects of Nutritional Intervention on Insulin Resistance–Associated Inflammatory Biomarkers and Gene Polymorphisms in Gestational Diabetes Mellitus: Nutritional Modulation of Inflammation and Insulin Resistance in GDM - Li, Jiayu; Sun, Lili; Zhang, Linjing (Journal of Medical Biochemistry, 2026)
Background: Insulin resistance is a central biochemical abnormality in gestational diabetes mellitus (GDM) and is closely linked to chronic low-grade inflammation. Pro-inflammatory cytokines and adipokines, including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and adiponectin (APN), play key roles in metabolic dysregulation during pregnancy. This study investigated the effects of nutritional intervention on insulin resistance–related inflammatory biomarkers and their gene polymorphisms in pregnant women with GDM. Methods: In this retrospective comparative cohort study, 400 pregnant women diagnosed with GDM at Hainan Women and Children’s Medical Center between October 2023 and December 2024 were enrolled and assigned to a conventional treatment group (CT, n = 200) or a nutritional intervention group (NC, n = 200). Both groups received standard glycemic management, while the NC group additionally underwent individualized nutritional intervention. Serum levels of TNF-α, IL-6, and APN were measured by enzyme-linked immunosorbent assay, and polymorphisms of the corresponding genes were analyzed using fluorescence quantitative PCR. Glycemic and lipid parameters were evaluated concurrently. Clinical efficacy and pregnancy outcomes were assessed as secondary endpoints. Results: The genotype distributions of TNF-α, IL-6, and APN showed no significant differences between the two groups (P > 0.05). Baseline inflammatory, glycemic, and lipid indices were comparable between groups. After intervention, both groups demonstrated significant improvements in inflammatory markers, blood glucose, and lipid profiles compared with baseline (P < 0.05). Notably, post-treatment levels of TNF-α and IL-6 were significantly lower, while APN levels were more favorably regulated in the NC group compared with the CT group (P < 0.05). The NC group also exhibited superior metabolic control and a lower incidence of adverse pregnancy outcomes. Conclusion: Nutritional intervention significantly improves insulin resistance–associated inflammatory and metabolic profiles in pregnant women with GDM, independent of TNF-α, IL-6, and APN gene polymorphisms. These findings highlight the biochemical benefits of nutritional modulation in attenuating inflammation and improving metabolic homeostasis in GDM.